2020
DOI: 10.3389/fpubh.2020.578438
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of the COVID-19 Pandemic on Future Birth Rate

Abstract: Here, we examine the potential effect of the COVID-19 pandemic on future birth rates. This highly contagious disease originated in China, and rapidly spread worldwide, leading to extensive lockdown policies being implemented globally with the aim of containing the infection rates and its serious attendant consequences. Based on previous extant literature, this paper overviews the potential demographic consequences of the current progressively widespread epidemic on conception and fertility as driven by the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 35 publications
4
64
1
5
Order By: Relevance
“…The 1918 influenza pandemic led to a sharp reduction in U.S. births, with recovery on a period basis in the years that followed (Wagner et al 2020). More recently, epidemics have generally been associated with declines in fertility at least in the short term, provided access to contraception is not severely limited (Ullah et al 2020). With regard to economic changes, recent cohorts of U.S.…”
Section: Baby Bust: Falling Fertility In Us Counties Is Associated Wimentioning
confidence: 99%
“…The 1918 influenza pandemic led to a sharp reduction in U.S. births, with recovery on a period basis in the years that followed (Wagner et al 2020). More recently, epidemics have generally been associated with declines in fertility at least in the short term, provided access to contraception is not severely limited (Ullah et al 2020). With regard to economic changes, recent cohorts of U.S.…”
Section: Baby Bust: Falling Fertility In Us Counties Is Associated Wimentioning
confidence: 99%
“…Thus, the results might represent a difference between generality and specificity when eliciting responses: Asking participants to "think about the last 6 months" required a more specific examination of their immediate situation compared to the question "what is your ideal number of children?" Importantly, this supposition is supported by the data from previous pandemics where there is a brief reduction in births before a "boom" (Ullah et al, 2020). Thus, asking participants to consider their immediate circumstances produced different responses compared to asking a general question about family planning.…”
Section: Extrinsic Risk and Reproductive Decision-making (Covid-19 Experience)mentioning
confidence: 87%
“…The duration of each window of opportunity is limited and does not last forever. Instead, the realization of demographic dividends depends on appropriate policies adopted in other related sectors and the country's ability to implement these policies (22). Research has shown that female labor force participation, educational attainment of the labor force, the potentiality of the old-age population entering the workforce, people's health and wellbeing, urbanization, investments (especially foreign direct invests), high technology, and international trades are all important factors determining the outcomes of demographic dividends (22).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the realization of demographic dividends depends on appropriate policies adopted in other related sectors and the country's ability to implement these policies (22). Research has shown that female labor force participation, educational attainment of the labor force, the potentiality of the old-age population entering the workforce, people's health and wellbeing, urbanization, investments (especially foreign direct invests), high technology, and international trades are all important factors determining the outcomes of demographic dividends (22). It is thus important for different countries to formulate socioeconomic policy packages that are consistent with their own population trends and characteristics to reap the maximum benefits of the demographic dividends.…”
Section: Discussionmentioning
confidence: 99%